2018
DOI: 10.1155/2018/7097540
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Events Associated with Inhaled Corticosteroid Treatment in Patients with Chronic Obstructive Pulmonary Disease: A Meta-Analysis

Abstract: Background The cardiovascular (CV) safety of inhaled corticosteroids (ICSs) in chronic obstructive pulmonary disease (COPD) is controversial because different studies have suggested that ICSs either increase or reduce the risk of CV events in COPD patients. In this meta-analysis, we assess the CV safety of ICS therapy in COPD. Methods A meta-analysis of randomized, double-blind, parallel-group, placebo-controlled trials of ICS treatment for COPD that include at least 4 weeks of follow-up was performed. A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
4
1
Order By: Relevance
“…Comparisons 3a and 3b (ICS-dose effects) and Comparisons 4a and 4b (intra-class effects) did not reveal any differences in the adverse event frequencies between the comparison groups, beyond those expected to arise by chance (Table 4). Results from the ICS-dose comparisons are consistent with findings from a meta-analysis of 31 trials in COPD, where the frequency of cardiovascular events was not different between the ICS-treated and control groups (risk ratio = 0.99; 95% CI: 0.93 to 1.06) [29]. Intra-class effects are also not expected based on data external to the present clinical development program.…”
Section: Ics-dose Effects and Intra-class Effectssupporting
confidence: 84%
“…Comparisons 3a and 3b (ICS-dose effects) and Comparisons 4a and 4b (intra-class effects) did not reveal any differences in the adverse event frequencies between the comparison groups, beyond those expected to arise by chance (Table 4). Results from the ICS-dose comparisons are consistent with findings from a meta-analysis of 31 trials in COPD, where the frequency of cardiovascular events was not different between the ICS-treated and control groups (risk ratio = 0.99; 95% CI: 0.93 to 1.06) [29]. Intra-class effects are also not expected based on data external to the present clinical development program.…”
Section: Ics-dose Effects and Intra-class Effectssupporting
confidence: 84%
“…Our findings contradict the findings of a previous metaanalysis by Xia Jing et al 6 The previous meta-analysis found no increased risk of cardiovascular events in COPD patients on ICS-containing medications compared with controls.…”
Section: Risk Of Biascontrasting
confidence: 99%
“…A metaanalysis of 31 RCTs, with at least 4 weeks of follow-up, found no association between ICSs (in any combination) and CVD (relative risk 0.99, 95% confidence interval [CI] 0.90 to 1.90). 6 An additional systematic review published in 2009 included both RCTs and observational studies and found no association between ICSs and CVD in RCTs (relative risk 1.02, 95% CI 0.81 to 1.27), however, in 2 observational studies a protective effect of ICSs was seen on CVD mortality (relative risk 0.79, 95% CI 0.72 to 0.86). 7 This systematic review, however, was published in 2009 and there have been many more observational studies and RCTs published since then.…”
mentioning
confidence: 99%
“…Daily use of ICSs has been proved to decrease the frequency of exacerbations and improve quality of life in patients with FEV 1 less than 50% predicted [ 1 , 4 ]. However, daily use of ICSs may cause drug-related adverse events, such as increased risks of fracture and infections [ 32 , 33 ], but may not increase the risk of cardiovascular events [ 34 ]. URTI is the most common respiratory infections and also an important cause of exacerbation of COPD.…”
Section: Discussionmentioning
confidence: 99%